Pengelolaan Akun Instagram @info.unidha Sebagai Bagian Dari Media and Content Department Universitas Dharma Andalas (Max 12 Kata: Bahasa Indonesia) - Ramadhani, Devina; Flowerina, Indria (CV. ITTC INDONESIA, 2024)
This final project report is made as a description of the work done while being part of the Media and Content Department (MCD) at Dharma Andalas University. The Media and Content Department was formed with the aim of carrying out campus promotion activities at Dharma Andalas University in order to achieve the goal of increasing the number of new students in 2023 and introducing the campus to the community, especially young people who use Instagram as social media. While being part of the Media and Content department, the activities carried out and implemented are creating content as a source of campus information and majors at Dharma Andalas University and interacting with Instagram account followers to be interested in the content that has been and will be created so that the objectives of promotion are achieved. The theory used in applying the implementation of the Media and Content Department's work program is Public Relations Management.